To compare the efficacy of two different bolus doses of phenylephrine in combination with oxytocin in preventing oxytocin-induced hypotension during cesarean section under spinal anesthesia: A randomized comparative study - Snehalata Kumari; Ratindra K Barman; Pranab Kalita; Peter Engti (Wolters Kluwer Medknow Publications, 2023)
Background: A randomized comparative study was conducted to assess the effectiveness of two different bolus doses of phenylephrine to obtund the hypotensive effects of bolus oxytocin injection in patients undergoing cesarean section under spinal anesthesia. Methods: The study involved 180 parturients belonging to the ASAI and II, undergoing CS under SA were randomized into three groups, group A: oxytocin 3U and phenylephrine 50 μg; group B: oxytocin 3U and phenylephrine 75 μg; group C: oxytocin 3U and normal saline, administered intravenously over 5 min after delivery of anterior shoulder. The incidence of hypotension being the primary objective and hemodynamic changes, the incidence of nausea and vomiting, and other complications, such as total rescue vasopressor requirement, adequacy of uterine contraction, and the number of patients requiring additional uterotonics, were our secondary objectives. Results: The incidence of hypotension was highest in group C (83.3%) followed by group A (80%) and lowest in group B (11.6%). The total rescue doses of PE after T0 between the three groups showed that group A required (61.32 ± 41.19) μg, group B required (10.19 ± 29.75) μg, and group C required (113.21 ± 47.18) μg of PE. The uterine contraction was comparable between the groups. Incidence of nausea and vomiting and other complications were comparable between the groups. Conclusion: Co-administration of PE 75 μg with OT 3 IU after delivery reduces the incidence of OT-induced hypotension and rescue vasopressor requirement compared to co-administration of 50 μg PE during CS under spinal anesthesia.